Initial meeting: Criteria for the selection of adult education training techniques - Georgas, Thomas; Giannoukos, Georgios; Stergiou, Ioannis; Kallianta, Sotiria; Hioctour, Vasilios; McCormick, Michael (IJRDO- Journal of Educational Research, 2018)
The first contact of the trainer with the trainees is a very important moment during a program. Its outcome will determine whether the trainees are interested in the program and will get actively involved and on the other hand, if the trainer himself feels he is acting in a creative environment that will affect his/her performance during the program. For this reason, a text that will describe and give guidance for the first meeting must be carefully designed, considering of all factors for an effective kick-off meeting.